Pemanfaatan Pojok Literasi sebagai Media Kreativitas dalam Pengembangan Bakat Siswa MI Mambaul Ulum Dagan - Apriliya, Erika Putri; Suradji, Muchammad; Shoimah, Retno Nuzilatus (Madrasah Ibtidaiyah Education Journal, 2025)
Education has a strategic role in forming future generations who are able to face the challenges of the times, especially in the context of globalization and technological progress. This research focuses on the use of literacy corners as a medium for creativity in developing students' talents at Madrasah Ibtidaiyah (MI) Mambaul Ulum Dagan. Through a qualitative descriptive approach, this research explores how literacy corners can increase students' reading interest and creativity. The research results show that a well-designed literacy corner, equipped with a varied collection of books, is able to create an inspiring learning environment. Students show improvement in the ability to express creative ideas through writing and visual arts. In addition, support from parents and collaboration between schools and libraries contribute to the success of this program. This research recommends implementing the model of utilizing literacy corners in other schools as an effort to develop students' creativity and talents more effectively. Thus, the literacy corner not only functions as a reading source, but also as a means to stimulate students' imagination and potential, which ultimately contributes to a better quality of education